2000
DOI: 10.1007/bf03402116
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunological Properties of a Viral Hybrid Particle Expressing the Plasmodium vivax Merozoite Surface Protein 1 C-terminal Region

Abstract: most solid subunit vaccine candidates against the asexual blood stages of malaria, although its function remains elusive (1). Experiments in rodents, Aotus and Saimiri monkeys, either with the affinity-purified, yeast-, bacteria-or cell culturederived MSP1 19 , showed protection against blood stage challenge with P. falciparum (2), P. vivax (3), P. cynomolgi (4), and P. yoelii (5). Recently, a phase 1 clinical trial was reported (6). Since protection is mostly antibody-dependent (1),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Importantly, even the 50 kDa fusion of PfRH5 to HBsAg seemed to elicit the production of 20–25 nm particles in transfected cells as detected by dynamic light scattering analysis ( Figure S3 ). When directly comparing the obtained antibody titers against PvMSP1 19 , we did not observe significantly higher titers using the liposomal approach compared to a study using the construct as a naked, intramuscularly delivered DNA vaccine 30 . Nevertheless, the herein achieved titers were much higher compared to the genetic vaccination of either CS 31 or MSP1 19 alone, 32 underlining the enhancing effect of HBsAg in the construct.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Importantly, even the 50 kDa fusion of PfRH5 to HBsAg seemed to elicit the production of 20–25 nm particles in transfected cells as detected by dynamic light scattering analysis ( Figure S3 ). When directly comparing the obtained antibody titers against PvMSP1 19 , we did not observe significantly higher titers using the liposomal approach compared to a study using the construct as a naked, intramuscularly delivered DNA vaccine 30 . Nevertheless, the herein achieved titers were much higher compared to the genetic vaccination of either CS 31 or MSP1 19 alone, 32 underlining the enhancing effect of HBsAg in the construct.…”
Section: Discussioncontrasting
confidence: 71%
“…Importantly, the doses used for immunization herein were much smaller, and the uniformity in antibody titers in individual mice was much improved. 30 Liposomal DNA vaccination involving HBsAg is supposed to stimulate antigen presentation by primary dendritic cells in both MHC1 and MHC2 receptors. 34 Although not tested for, it is therefore expected that antigen-specific T and B cells, including memory cells, are developed and that immune response can be boosted upon contact with the native antigens during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Survival occurred in 5 of 12 animals. Most likely, the HBs moiety plays a crucial role in this protection since we had previously demonstrated that HBs augmented the antigenicity of a plasmid encoding the MSP1 19 from P. vivax (10) and that it was able to form a viral hybrid particle (28). Moreover, a widely recognized T-helper-cell epitope is contained in the HBs domain (11).…”
Section: Discussionmentioning
confidence: 99%
“…A similar construct for the P. vivax MSP1 19 had been previously shown to be highly antigenic (10) and to form hybrid viral particles (28). Moreover, since an effective immune response against blood stage infection of mice with P. chabaudi has a Th1 profile (24), we also coinjected plasmid vectors coding for Th1-associated cytokines, namely, murine interleukin-2 (IL-2), gamma interferon (IFN-␥), and granulocyte-macrophage colony-stimulating factor (GM-CSF).…”
mentioning
confidence: 99%
“…The merozoite surface 1 protein of the malarial parasite Plasmodium vivax [41], HIV gp120 [38], dengue virus type 2 envelope protein [37], and the E7 oncoprotein of human papillomavirus type 16 [20], have all been attached to the C'-terminus of HBsAg. All these C'-terminally extended recombinant HBsAg molecules retained the capacity to form VLPs or VLP-like structures, which were immunogenic, or at least antigenic, for the inserted foreign protein.…”
Section: Extensions At the C' Terminusmentioning
confidence: 99%